PERSEPSI MAHASISWA TERHADAP KUALITAS PELAYANAN FAKULTAS EKONOMI UNIVERSITAS 17 AGUSTUS 1945 SAMARINDA - Putera, Deny Ryan (EKONOMIA, 2013)
DENYÂ  RYAN PUTERA, Under the guidance of the Mr. Robin Jonathan and Mrs. Suyatin.The method of analysis used by the author is used Cartesian diagram, which is a diagram that is divided up into 4 sections (often referred to as the square) are bounded two perpendicular lines that intersect at points X and Y axis average.Based on the research results of the calculation of the level of compatibility between the services received by the student expectation that migrants concrete manifestation aspect = 87.97%, TKI = 81.52% reliability aspects, aspects TKI responsiveness = 79.69%, workers assurance aspect = 88, 23%, TKI aspects of empathy = 85.08%, and the workers on the average - average overall aspect = 84.41%. So are all less than 100% means that the general student at the Faculty of Economics, University of Samarinda August 17, 1945 have not been satisfied with the services of the Faculty of Economics, University 17 August 1945 Samarinda.Â